Uniforms of Empire: The Intersection of Race, Religion, and Sartorial Politics in Napoleon’s Egyptian Campaign - Tania Sheikhan (Religions)
This article examines the ideological significance of the Kashmir shawl during Napoleon’s Egyptian campaign (1798–1801), focusing on depictions in Antoine-Jean Gros’ Bonaparte Visits the Plague-stricken in Jaffa and Andre Duterte’s portrayals of French soldiers for Descriptions de l’Egypte. Tracing the shawl’s transformation from an Islamic artefact to a French military accessory and later a symbol of domestic luxury, this study highlights its dual role as a site of cultural negotiation and a tool of colonial domination. Through its exploration of the Kashmir shawl, this article contributes to a deeper understanding of the intersections of race, religion, and ethnicity, demonstrating how material culture both mediated and reinforced power dynamics within Napoleon’s imperial project.